Aquatic photochemistry of Cu(II) in the presence of As(III): Mechanistic insights from Cu(III) production and As(III) oxidation under neutral pH conditions. (1st December 2022) - Wu, Yi; Guo, Juntao; Zhang, Yihui; Xu, Jing; Pozdnyakov, Ivan P.; Li, Jinjun; Wu, Feng
Research highlights: Insight into photochemistry of Cu(II) in the presence of As(III) at pH 7 was provided. Simultaneous As(III) oxidation and Cu(II) reduction were observed. The LMCT process occurs between Cu(II) and As(III) in their surface complex. Cu(III) produced from the Cu(I)-Fenton reaction oxidizes As(III) efficiently. The reaction process was modeled by kinetic analysis and simulation. Abstract: Surface complexation between arsenite (As(III)) and colloidal metal hydroxides plays an important role not only in the immobilization and oxidation of As(III) but also in the cycle of the metal and the fate of their ligands. However, the photochemical processes between Cu(II) and As(III) are not sufficiently understood. In this work, the photooxidation of As(III) in the presence of Cu(II) under neutral pH conditions was investigated in water containing 200 μM Cu(II) and 5 μM As(III) under simulated solar irradiation consisting of UVB light. The results confirmed the complexation between As(III) and Cu(II) hydroxides, and the photooxidation of As(III) is attributed to the ligand-to-metal charge transfer (LMCT) process and Cu(III) oxidation. The light-induced LMCT process results in simultaneous As(III) oxidation and Cu(II) reduction, then produced Cu(I) undergoes autooxidation with O2 to produce O2 ⁻ and H2 O2, and further the Cu(I)-Fenton reaction produces Cu(III) that can oxidize As(III) efficiently ( kCu(III) + As(III) = 1.02 × 10 9 M –1 s –1 ). The contributions from each pathway ( ρrCu(II)-As(III)+hv = 0.62, ρrCu(III) + As(III) = 0.38) were obtained using kinetic analysis and simulation. Sunlight experiments showed that the pH range of As(III) oxidation could be extended to weak acidic conditions in downstream water from acid mine drainage (AMD). This work helps to understand the environmental chemistry of Cu(II) and As(III) regarding their interaction and photo-induced redox reactions. Graphical Abstract: Image, graphical abstract